2017
DOI: 10.3390/ijms18030600
|View full text |Cite
|
Sign up to set email alerts
|

The Development of a Novel Therapeutic Strategy to Target Hyaluronan in the Extracellular Matrix of Pancreatic Ductal Adenocarcinoma

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is one of the most lethal diseases to affect humans, regardless of whether patients receive multimodal therapy (including surgery, radiotherapy, and chemotherapy). This resistance to intervention is currently considered to be caused by the desmoplastic change of the extracellular matrix (ECM) in PDAC tissues, which is characterized by the accumulation of cancer-associated fibroblasts, collagen, proteoglycan, and hyaluronan. Among these ECM components, hyaluronan has attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 79 publications
1
24
0
1
Order By: Relevance
“…A positive effect of 4-MU treatment was also reported on the sensitivity of fibrosarcoma cells to radiotherapy (Saga et al, 2017). Under the trade name Hychromone, 4-MU is already marketed in Asia and Europe as a choleretic agent (reviewed in Kudo et al, 2017). As clinical experience with this drug already exists, application in a different cancer treatment setting could be probably enhanced.…”
Section: Targeting Hyaluronan Synthesismentioning
confidence: 97%
“…A positive effect of 4-MU treatment was also reported on the sensitivity of fibrosarcoma cells to radiotherapy (Saga et al, 2017). Under the trade name Hychromone, 4-MU is already marketed in Asia and Europe as a choleretic agent (reviewed in Kudo et al, 2017). As clinical experience with this drug already exists, application in a different cancer treatment setting could be probably enhanced.…”
Section: Targeting Hyaluronan Synthesismentioning
confidence: 97%
“…Liver cancer metastasis is an extremely complex "multi-step" process, liver cancer cells leave the primary tumor and invaded into blood vessels and lymphatic vessels through the extracellular matrix (extracellular matrix, ECM), then the metastases was formed [16]. In this process, the combination of hepatoma cells and ECM is the initial step of invasive growth and distant metastasis of hepatocarcinoma cells [17]. A recent study showed that OM inhibits hepatocyte apoptosis by suppressing the TLR4/PI3K/Akt/GSK-3β signalling pathway [18].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of HA in the TME has previously been shown to increase tumor interstitial pressure, inducing vascular collapse, which was associated with a decreased exposure of tumor cells to chemotherapy. Conversely, removal of HA in the TME can reverse these physiologic characteristics and, ultimately, improve accessibility of the tumor cells to chemotherapy in various mouse models of pancreatic ductal adenocarcinoma (15,(26)(27)(28)(29). Furthermore, it was shown that depletion of HA can lead to an increased accumulation of CD8 þ T cells in tumors of a mouse model of ovarian cancer (30).…”
Section: Introductionmentioning
confidence: 99%